Competence-Based Educational Cluster Model for Developing Future Physics Teachers toward Quality Education to support Sustainable Development Goals (SDGs) - Tillaboyev Azlarkhan Magbarkhanovich; Eshniyozov Umid Akhrolivech; Fayazova Diloram To’ychiyevna; Adas Sultanova; Umbarov Abduvahid Uktam; Israilov Shermurod Shamsiddin; Khudoyberdieva Yulduz Khairulla; Munisa Jabbor Eshbekova (ASEAN Journal of Educational Research and Technology, 2026)
This study aims to design a competence-based educational cluster model that enhances the professional development of future physics teachers. The research employs analytical and comparative methods to examine international practices and national policies on teacher education. Results indicate that cluster-based collaboration strengthens innovation, improves teacher readiness, and aligns educational standards with sustainable development principles. This integration is significant because it promotes the continuous growth of professional competence and connects education with labor market needs. The model reflects the principles of SDG 4 on quality education by fostering inclusive and equitable learning environments. The study concludes that educational clusters offer a sustainable pathway for improving teacher competence, promoting lifelong learning, and enhancing global academic cooperation.